Covering Shame, Sacrificing Rights: A Maqāṣid al-Shari’ah Perspective on Child Protection in Incestuous Marriage Practices - Ricy Fatkhurrokhman; Muhammad Royhan Assaiq; Tri Wastuti (Indonesian Academy of Social and Religious Research (IASRR), 2025)
This study examines the practice of marriage after incest to cover up family shame in Sendang 1, Gunungkidul, through the perspective of maqāṣid alsyarī‘ah and child protection. This study aims to highlight how these practices, which are intended to maintain family dignity, violate the main principles of maqāṣid al-syarī‘ah, particularly ḥifẓ al-nafs (protection of life), ḥifẓ alnasl (protection of offspring), and ḥifẓ al-’ird (protection of honour). Using a qualitative approach with descriptive-analytical methods, this study analyses the case of a 16-year-old girl who was forced to marry after becoming pregnant by her brother, highlighting the detrimental impact on her psychological and physical well-being. The results of the study show that such practices not only contradict Islamic teachings but also violate national and international child protection laws, including the principle of the best interests of the child. This study presents a new conceptual framework that integrates maqāṣid al-sharī’ah with child protection laws, advocating for reforms in Islamic family law to prioritise the protection and rights of children.